The Effect of Polishing Techniques and Time on the Surface Characteristics and Sealing Ability of Resin Composite Restorations After One-year Storage - Maximiliano Sérgio Cenci; Daniela Venturini; Tatiana Pereira‐Cenci; Evandro Piva; Flávio Fernando Demarco (2008)
Since there is a lack of information on the surface properties of composite restorations achieved with standard polishing procedures after aging processes, this study evaluated the effects of immediate (IM) and delayed (DE) polishing on the surface roughness (Ra), microhardness (KHN) and microleakage (ML) of microfilled (Filtek A110) and hybrid (Filtek Z250) resin composites after one-year storage. Standardized preparations were made on the buccal surface of 256 bovine teeth, where half were restored with each composite. For each composite, the specimens were randomly allocated to two subgroups. The first group (IM) was polished immediately after gross finishing using three different systems/techniques (n=16): Sof-Lex, Flexicups and Flexicups + Jiffy Polishing Brush + Flexibuffs (sequential), then stored for three weeks in saline. The DE group was stored for two weeks, polished with the same systems and stored for one week. From each subgroup, eight specimens were assessed after three weeks regarding Ra, KHN and ML (baseline), andthe eight remaining specimens were stored for one year before analysis. The data were analyzed (alpha=0.05) with ANOVA, paired Student's t-test (Ra and KHN) or Kruskal-Wallis and Signed Rank tests (microleakage). After one year, microfilled resin composite specimens showed the lowest Ra and KHN (p<0.05). N o differencein microleakage was observed among the different groups (p>0.05). The sequential technique provided the lowest roughness and Sof-Lex the lowest hardness (p<0.05). IM showed similar or better performance than DE for ML and Ra (p<0.05). In conclusion, aging increased the composites Ra and ML in all experimental conditions (p<0.05).